Proposta de implantação do sistema de gestão ambiental (SGA) em uma oficina mecânica de pequeno porte no Município de Passo Fundo - Mognon, Suelen (2022)
Mechanical workshops are establishments from the automotive sector, where they are responsible for automotive repair and maintenance, services such as oil and lubricating fluid changes, electrical components, engine rectification, replacement and cleaning of parts, and general maintenance. Thinking about the point of view, the activities generated within the workshops have a great polluting potential, offering several risks, both for soil, air and water contamination. In this sense, environmental management is of great importance so that adequate monitoring of this sector can be carried out, in order to reduce any risk or possible environmental impact. For small companies, the ISO 14001/2015 standard can be used as support, which presents the requirements for the implementation of an Environmental Management System (EMS). The present work proposes the application of an environmental management system in a mechanical workshop in the city of Passo Fundo (RS), for this purpose, a documental survey of the company and the legal requirements applicable to this enterprise was carried out, with a total of 32 requirements raised, identified the 15 areas present in the place, the survey of the environmental impacts caused by its activities resulted in 68 identified divided into 5 categories, being the most expressive in the generation of waste, 46 aspects were identified divided into 6 categories, the class of waste most generated on site are from I – hazardous waste, after which mitigation measures were proposed in order to minimize their impacts. The methodology was being developed in weekly technical visits to the site, observing its activities, interviewing employees and the owner, in order to better understand the operation and needs of the site. When carrying out the environmental impact survey, it is observed, among them, atmospheric emissions, effluent generation, waste generation and use of natural resources, and the ones with the greatest impacts are the generation of effluents from oil and lubricant changes and waste generation, the aspects arising from these impacts are diverse, including: changes in the quality of air, soil and water.